(untitled) (Iraqi Journal of Medical Sciences, 2016)
Background:Aging of testis is gradual dysfunction of body organs and tissues due to reduction of cell number and loss of cell capacity for reproduction and regeneration of its structural elements. Objective:To study the age related changes of the human testes anatomically and histologically. Methods:Forty testes of twenty adult Iraqi male cadavers, with age ranged from 20-69 years were taken from the Forensic Medicine Department of Tikrit and Azadi Teaching Hospital in Salahddin and Kirkuk province, respectively during the period from November 2006 to September 2007. The testicular specimens were divided into five groups according to cadaver age. Tunica albuginea was removed to investigate the lobular and tubular structures of the testis, by anatomical and histological procedures. Results:The gross metrical measurement and anatomical inspection revealed that a negative correlation was existed between the process of aging and the weight of the postmortem, testis. A strong directly proportional positive correlation was found between age and the thickness of basement membrane, interstitial spaces between seminiferous tubules. Tubular sclerosis was observed in some testis specimens of senescent cadavers associated with a decrease in the number of the lining epithelial cells of the seminiferous tubules and sclerotic changes in the walls of testicular blood vessels. Conclusion:The process of aging leads to testicular changes such as tubular diverticula and decrease in number of leydig cells. Key words:Aging, Leydig cells, senescent testis, seminiferous tubules.